Characterisation of the vaginal microflora of human immunodeficiency virus (HIV) positive and negative women in a sub-urban population of Kenya - Kiama, Teresa N.; Verhelst, Rita; Mbugua, Paul M.; Vaneechoutte, Mario; Verstraelen, Hans; Estambale, Benson B.; Temmerman, Marleen (African Journal of Biotechnology, 2013)
Lactobacilli predominate normal vaginal microflora and are important in maintenance of vaginal health. The current study set out to identify and compare culture isolates of vaginal microflora of human immunodeficiency virus (HIV) positive (HIV+ ) and HIV negative (HIV- ) women at different phases during menstrual cycle from a sub-urban population of Kenya. Seventy four (74) women, 41 HIV+ and 33 HIV- , followed up two consecutive menstrual cycles, had high vaginal swabs taken to prepare Gram stains for six visits and anaerobic cultures for four. All 751 isolates identified by t-DNA polymerase chain reaction (PCR) belong to 51 species. Species cultured more frequently in HIV+ participants were: Lactobacillus jensenii (p=0.01), Lactobacillus iners (p=0.02), Gardnerella vaginalis (p=0.01) and Peptoniphilus lacrimalis (p=0.01). Species cultured more frequently in HIV- women were Dialister micraerophilus (p=0.02) and Streptococcus agalactiae (p=0.04). Lactobacillus predominating both groups were Lactobacilli crispatus, L. jensenii, L. iners and Lactobacilli vaginalis. Bacterial vaginosis (BV) was equally high in HIV+ and HIV- women. Lactobacillus and BV-associated species were cultured more frequently in HIV+ women. Minor species differences were found. Predominant Lactobacillus in culture were L. crispatus, L. iners, L. jensenii and L. vaginalis. These women had lower concentrations of lactobacilli in vaginal microflora than observed in previous studies of Caucasian women.
Characterisation of the vaginal microflora of human immunodeficiency virus (HIV) positive and negative women in a sub-urban population of Kenya
Keywords: Vaginal microflora; human immunodeficiency virus (HIV); menstrual cycle; t-DNA polymerase chain reaction (PCR); culture; bacterial vaginosis